2022
DOI: 10.1002/chem.202201471
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Modification of Axial Coordination for Transition‐Metal Single‐Atom Electrocatalyst

Abstract: Single-atom catalysts (SACs) have emerged as a new frontier in areas such as electrocatalysis, photocatalysis, and enzymatic catalysis. Aided by recent advances in the synthetic methodologies of nanomaterials, atomic characterization technologies, and theoretical calculation modeling, various SACs have been prepared for a variety of catalytic reactions. To meet the requirements of SACs with distinctive performance and appreciable selectivity, much research has been carried out to adjust the coordination config… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 96 publications
0
20
0
Order By: Relevance
“…Recently, Liu et al summarized the axial coordination effect on SACs with a combination of experimental and theorical analyses with respect to the functionalization by chalcogen-, halogen-, and nitrogen-containing ligands . Interestingly, axial engineering of Fe–N–C SACs was realized via the coordination of axial pyrrolic N in the N-doped graphene to FeN 4 with the formation of FeN 5 .…”
Section: Electronic and Geometric Tailoring Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Liu et al summarized the axial coordination effect on SACs with a combination of experimental and theorical analyses with respect to the functionalization by chalcogen-, halogen-, and nitrogen-containing ligands . Interestingly, axial engineering of Fe–N–C SACs was realized via the coordination of axial pyrrolic N in the N-doped graphene to FeN 4 with the formation of FeN 5 .…”
Section: Electronic and Geometric Tailoring Engineeringmentioning
confidence: 99%
“…Recently, Liu et al summarized the axial coordination effect on SACs with a combination of experimental and theorical analyses with respect to the functionalization by chalcogen-, halogen-, and nitrogen-containing ligands. 103 Interestingly, axial engineering of Fe–N–C SACs was realized via the coordination of axial pyrrolic N in the N-doped graphene to FeN 4 with the formation of FeN 5 . 104 The FeN 5 configuration was confirmed by Fe K-edge XANES spectra and DFT calculations, which yields significantly higher Faradaic efficiency in the CO 2 RR and partial current density in comparison to FeN 4 SACs.…”
Section: Electronic and Geometric Tailoring Engineeringmentioning
confidence: 99%
“…However, theoretical and experimental results revealed that the high structure/electron symmetry of the M-N 4 moiety, resulting from its symmetrical planar structure, makes it chemically inert to a certain extent, thus reducing the kinetics of the catalytic reaction and hindering it. 39,132,135,136 Therefore, in order to tune the performance of M-N 4 active sites for eCO 2 RR, breaking the symmetrical electronic structure of M-N 4 via a reasonable adjustment of the coordination structure to optimize the electronic structure of the M-N 4 , and subsequently affecting the binding energies for eCO 2 RR intermediates have caught researchers' attention and have been developed in full swing. By tuning the coordination numbers and introducing second atoms (metal or non-metal), the d orbital of the metal site can be significantly tuned, affecting the catalytic activity for eCO 2 RR.…”
Section: C1 Products On Mof-derived Sacsmentioning
confidence: 99%
“…-Cl, -I). 85 For instance, Li and co-workers successfully introduced Cl atoms into the pristine S doped Fe-N 4 catalysts. 86 The extremely ultrahigh 4e À ORR activity surpassed that of the unmodied S doped Fe-N 4 catalyst and most reported single atom catalysts.…”
Section: Coordination Atoms In the Rst Coordination Shellmentioning
confidence: 99%